Pembuatan Buku Panduan Perpustakaan di Perpustakaan Universitas Dharma Andalas - Dayani, Putri; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed the design of the library in the guide books Dharma Andalas University Library. The purpose of this paper to design a library of guide books in the Library of the University of Dharma Andalas. The method used is descriptive qualitative research methods with data collection through direct observation to the field (observation) and interviews. The observations were made by direct observation to Dharma Andalas University Library to obtain the necessary data. Collecting data through interviews conducted with heads of libraries, librarians and users in Library of Dharma Andalas University. Based on the discussion can be concluded the steps in the manufacture of guide books in the library of Dharma Andalas University Library, as follows; (A) collecting data and information, (b) making a framework for writing, (c) the manufacture of cover, (d) the manufacture of the foreword, (e) the preparation of the contents, (f) the manufacture of the main contents of books, the main elements contained in guide book library is to make the first chapter that discusses briefly about the library, its vision and mission, the room layout library and the organizational structure, chapter II, which discusses the clock service, order, and types of library services, chapter III, classification of library materials, type of collection and procedures for borrowing and returning, chapter IV which discusses how to use opacs (g) makes the cover. It can facilitate the librarians in the library to socialize and faciliitate pemustaka pemustaka in using the library and find information.Keyword: guide book, service, library.